Peningkatan Hasil Belajar Pengolahan Data dengan Model Pembelajaran Kooperatif Tipe Jigsaw di Sekolah Dasar - Anggara Marza (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
Through this research, the authors applied the approach of cooperative learning model type Jigsaw for improving students’ learning outcomes. The purpose of this research was to describe the planning, implementation, and learning outcomes at SD Negeri 02 Timbalun, Padang. The subjects of the research were 6th grade students. From the results, it appeared that students’ learning outcomes increased. On the first cycle of lesson planning, improved from 67% to 92%, activity of students 70% become 91%, and learning outcomes was from 68% to 84%.